Analisis Daya Saing Ekspor Kopi Indonesia dan Vietnam di Pasar Asean - Sudrajat, Muthia Ardhini (Educationist: Journal of Educational and Cultural Studies, 2023)
Over the past 14 years, the exports of coffee from Indonesia and Vietnam have continuously experienced growth, especially in the case of coffee HS 090111 (Coffee, not roasted, not decaffeinated), to the ASEAN 5 market. This growth is driven by the increasing quantity and value of coffee exports from both Indonesia and Vietnam in recent years. The establishment of the Asean Economic Community (AEC) in early 2016 stimulated coffee exporters, such as Indonesia, to maintain their export quantities to the ASEAN 5, making it necessary to analyze the competitiveness of Indonesian coffee products in the ASEAN 5 market. To determine the extent to which the coffee exports of Indonesia and Vietnam can compete in the ASEAN 5 market, a Revealed Comparative Advantage (RCA) analysis is conducted. The analysis results show that the coffee exports of Indonesia and Vietnam in the ASEAN 5 market are competitive, with Indonesia having an average RCA value of 1.0529667, while Vietnam has a value of 8.4148667. The government is expected to enhance Indonesia's coffee exports to the ASEAN 5 market, considering the continuously growing demand for coffee from that market. This requires the implementation of strategic policies that can stimulate farmers to produce coffee more efficiently.